2016
DOI: 10.3390/ijms17111777
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Melatonin Improves Plant Iron Deficiency Tolerance via Increased Accumulation of Polyamine-Mediated Nitric Oxide

Abstract: Melatonin has recently been demonstrated to play important roles in the regulation of plant growth, development, and abiotic and biotic stress responses. However, the possible involvement of melatonin in Fe deficiency responses and the underlying mechanisms remained elusive in Arabidopsis thaliana. In this study, Fe deficiency quickly induced melatonin synthesis in Arabidopsis plants. Exogenous melatonin significantly increased the soluble Fe content of shoots and roots, and decreased the levels of root cell w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 56 publications
1
47
0
Order By: Relevance
“…It was observed that NO serves as a modulator of MEL accretion during the distal signaling response. Similarly, studies of Zhou et al showcased the interdependency between MEL and NO during iron (Fe) deficiency in Arabidopsis plants. In this study, it was observed that Fe deficiency quickly induced MEL biosynthesis.…”
Section: Mel‐mediated Stress Ameliorationmentioning
confidence: 88%
See 1 more Smart Citation
“…It was observed that NO serves as a modulator of MEL accretion during the distal signaling response. Similarly, studies of Zhou et al showcased the interdependency between MEL and NO during iron (Fe) deficiency in Arabidopsis plants. In this study, it was observed that Fe deficiency quickly induced MEL biosynthesis.…”
Section: Mel‐mediated Stress Ameliorationmentioning
confidence: 88%
“…Therefore, it was proposed that NO plays a key role in polyamine‐mediated signaling pathways. On similar lines, Zhou et al provided concrete evidence documenting that exogenous applied MEL improves plant Fe deficiency tolerance in Arabidopsis plants via increasing polyamine‐mediated NO production. MEL was shown to induce PA metabolism in cucumber plants while conferring chilling tolerance with the co‐participation of ABA via modulating the transcripts of genes regulating ABA metabolism .…”
Section: Mel‐mediated Stress Ameliorationmentioning
confidence: 92%
“…The NO signal up-regulates the expression of iron-related genes such as FIT1, FRO2, and IRT1, thereby inducing the reactivation of iron in the cell wall, and increased availability of soluble iron. These phenomena were completely suppressed in the polyamine-and NO-deficient plants [38]. The NO-melatonin crosstalk is therefore partially related to the polyamine-mediated signaling pathway.…”
Section: Regulatory Roles Of Melatonin and Nitric Oxide In Plant Growmentioning
confidence: 87%
“…Iron deficiency often causes chlorosis and inhibits normal plant growth [114]. The application of exogenous polyamines causes an increase in NO production, indicating that NO is a key intermediate in the polyamine-mediated signaling pathway [38]. NO can increase the soluble iron content, and ameliorate leaf chlorosis and oxidative stress.…”
Section: Regulatory Roles Of Melatonin and Nitric Oxide In Plant Growmentioning
confidence: 99%
“…Furthermore, Fe deficiency quickly induced melatonin biosynthesis in Arabidopsis plants, acting synergistically with exogenous treatments. In mutant plants deficient in polyamine and nitric oxide (NO) biosynthesis, the protective role of melatonin was not observed, indicating that the process is dependent on the polyamine induced NO production under Fe deficient conditions [84]. In a similar work, tomato seedlings grown in an S deficient medium suffered serious growth inhibition as a result of a reduced chlorophyll content, photosynthesis, and biomass accumulation; it also led to cell structural alterations and DNA damage.…”
Section: Metals As a Severe Abiotic Stress And Effects Induced By Melmentioning
confidence: 98%